2008
DOI: 10.1124/jpet.108.146464
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Potent, and Selective GABACAntagonists Inhibit Myopia Development and Facilitate Learning and Memory

Abstract: This study reports pharmacological and physiological effects of cis-and trans-(3-aminocyclopentanyl)butylphosphinic acid . These compounds are conformationally restricted analogs of the orally active GABA B/C receptor antagonist (3-aminopropyl)-n-butylphosphinic acid (CGP36742 or SGS742). cis- [IC 50 (1) ϭ 5.06 M and IC 50 (2) ϭ 11.08 M; n ϭ 4] and trans-3-ACPMPA [IC 50 (1) ϭ 72.58 M and IC 50 (2) ϭ 189.7 M; n ϭ 4] seem competitive at GABA C receptors expressed in Xenopus laevis oocytes, having no effect as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 35 publications
(53 reference statements)
1
65
0
Order By: Relevance
“…GABA C receptor antagonists have also been useful experimental tools for demonstrating a role for these receptors in learning and memory [49,50,54]. TPMPA and the structural analog P4MPA ((piperidin-4-yl)methylphosphinic acid) were shown to enhance short-term memory in a bead discrimination task following injection into the multimodal association forebrain area in chicks [49].…”
Section: Gaba and Glutamate -New Developments In Neurotransmission Rementioning
confidence: 99%
See 2 more Smart Citations
“…GABA C receptor antagonists have also been useful experimental tools for demonstrating a role for these receptors in learning and memory [49,50,54]. TPMPA and the structural analog P4MPA ((piperidin-4-yl)methylphosphinic acid) were shown to enhance short-term memory in a bead discrimination task following injection into the multimodal association forebrain area in chicks [49].…”
Section: Gaba and Glutamate -New Developments In Neurotransmission Rementioning
confidence: 99%
“…form-deprivation myopia [51], while (3-aminopropyl)-n-butylphosphinic acid (CGP36742 or SGS742) was found to inhibit the development of myopia in chicks [50]. Thus, TPMPA and related GABA C receptor antagonists have been suggested for the treatment of myopia, administered intravitreally, orally, and ophthalmically [52].…”
Section: Gaba and Glutamate -New Developments In Neurotransmission Rementioning
confidence: 99%
See 1 more Smart Citation
“…In continuation of our efforts to identify the role of GABA C receptors in the CNS, we discovered that the selective GABA C receptor antagonists, cis-and trans-(3-aminocyclopentanyl)-n-butylphosphinic acid (cis-3-ACPBPA 4 and trans-3-ACPBPA 5; Figure 1), inhibit myopia progression in chicks and facilitate learning and memory in the Morris Water Maze task in rats. 19 The discovery of potent and selective GABA C antagonists emphasizes some important pharmacological differences between these GABA receptor families. Thus, GABA C receptors may be of clinical and pharmacological interest as potential therapeutic targets for myopia, in enhancing cognition and managing memory-related disorders, and its presence in the amygdala might be an alternative target for the development of antianxiety drugs.…”
mentioning
confidence: 99%
“…We cannot but speculate whether Graham's continued interest in the actions of therapeutically beneficial, dietary flavonoids at the GABA A receptor is fuelled by a love of fine food and wine [6,7]. More recently his work has led to the definition of the GABA C receptor [8], which appears to represent a therapeutic target for myopia and in enhancing cognition and in managing memory-related disorders [9]. Other early studies showed the way towards defining the multiple subtypes of ionotropic receptors for L-glutamate [10,11].…”
mentioning
confidence: 99%